Uso antenatal de corticosteóide e evolução clínica de recém-nascidos pré-termo - Martinez, Francisco Eulogio; Linhares, Nelson J.; Ferlin, Maria L. S.; Marba, Sérgio; Netto, Abimael A.; Procianoy, Renato S.; Uchoa, Natacha T.; Lopes, José Maria A.; Bomfim, Olga; Guinsburg, Ruth; Almeida, Maria Fernanda B.; Miyoshi, Milton; et al. (Sociedad Chilena de Pediatria, 2006)
Objectives: To describe the use of antenatal corticosteroid and clinical evolution of preterm babies. Methods: An observational prospective cohort study was carried out. All 463 pregnant women and their 514 newborn babies with gestational age ranging from 23 to 34 weeks, born at the Brazilian Neonatal Research Network units, were evaluated from August 1 to December 31, 2001. The data were obtained through maternal interview, analysis of medical records, and follow-up of the newborn infants. Data analysis was performed with the use of chi-square, t Student, Mann-Whitney, and ANOVA tests and multiple logistic regression, with level of significance set at 5%. Results: Treatment was directly associated with the number of prenatal visits, with maternal hypertension and with the antenatal use of tocolytic agents. Babies from treated pregnant women presented better Apgar scores at the 1st and 5th minute, reduced need for intervention in the delivery room and lower SNAPPE II. They were born with higher birth weight, longer gestational age and needed less surfactant use, ventilation, and oxygenation time. After multiple logistic regression, the use of antenatal corticosteroid independently improved birth conditions, decreased ventilation time, being related to increased occurrence of neonatal sepsis. Conclusions: The use of corticosteroid was associated with better prenatal care and birth conditions, better preterm evolution but higher risk of infection. © 2007 Sociedad Chilena de Pediatría.
Antenatal corticosteroid use and clinical evolution of preterm newborn infants
Keywords: Antenatal glucocorticoids; Infection; Low birth weight; Mechanical ventilation; Prematurity; corticosteroid; uterus spasmolytic agent; Apgar score; birth weight; cohort analysis; gestational age; human; infant; interview; low birth weight; maternal hypertension; medical record review; oxygenation; pregnant woman; prematurity; sepsis